Trades access common core. Line D. Organizational skills; Competency D-3 Read Drawings and Specifications - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"Some of the most important documents used in the workplace are the technical drawings, diagrams, and schematics that specify how fabrication and construction tasks will be carried out, or describe the composition and assembly of equipment. One of the essential skills for anyone involved in a trade is the ability to correctly interpret drawings. If you are in a construction or fabrication industry, you will need to be able to examine a drawing, take information from it, and visualize the finished product. If you are in a service or maintenance industry, you will need to interpret exploded drawings in order to properly repair or assemble equipment"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Architecture -- Designs and plans -- Textbooks; Electronic books